The Effect of Skin-to-Skin Contact Between Father and Baby on Paternal Attachment - Yilmaz, Mine Erdoğan; Korukcu, Oznur; Kabukcuoglu, Kamile (Current Psychiatry Research and Reviews, 2022)
Aim: This study aims to determine the effect of skin-to-skin contact between father and baby within the first three hours following childbirth on the level of paternal attachment. Methods: Data were collected from 69 fathers between May-July 2018 with paternal infant attachment scale in Antalya Medical Park Hospital in Turkey in this quasi-experimental study. Results: Total score of the fathers who established skin-to-skin contact with the babies was 82.34±7.76, and that of the control group was 66.07±18.2 (p<0.05). Moreover, the paternalinfant attachment level of the fathers in the study group who became fathers for the first time was higher than that of the control group. Conclusion: The skin-to-skin contact between father and baby following childbirth was an effective practice in the transition to fatherhood.
Keywords: skin-to-skin care